COLLABORATIVE GOVERNANCE IN THE REVITALIZATION OF CADIKA PARK TO REALIZE PUBLIC OPEN SPACE IN MEDAN CITY - Fitri Nuraisyah; Muhammad Imanuddin Kandias Saraan (Academic Solution Publisher, 2025)
This study examines the implementation of collaborative governance in the revitalization of Taman Cadika as a public open space in Medan City. The revitalization of urban parks is considered crucial because public spaces function as venues for social interaction, community recreation, and the improvement of environmental quality, while also supporting the city’s image through adequate facilities and services. This research employed a qualitative approach with a descriptive design, conducted at the Medan City Youth and Sports Office, the Taman Cadika area, and the Medan City Development Planning Agency (Bappeda). Data were collected through interviews, observation, and documentation, with informants selected using purposive sampling involving key, main, and supporting informants. The findings indicate that the revitalization of Taman Cadika is a collaborative process involving the government, the private sector, and the community, with central dynamics reflected in the integration of shared principles, joint motivation, and collective capacity for action. CSR funding support from PT Tor Ganda strengthened the implementation of the revitalization program; however, the study also reveals post-revitalization management challenges, particularly in monitoring facilities and ensuring visitor compliance. This study highlights that the sustainability of public open spaces after revitalization is strongly influenced by adaptive management, stronger monitoring procedures, and increased public participation and awareness.